Trial of a prehospital intervention with traditional Chinese medicine for acute stroke (TRACE): Protocol for a mixed-methods research study - Yuanyuan Chen; Ziyu Tian; Shuyan Wang; Hongmei Liu; Yanfang Liu; Wei Peng; Xinxing Lai; Dahe Qi; Lingbo Kong; Lingbo Kong; Ying Gao; Ying Gao (Frontiers Media S.A., 2022)
Background: As the only traditional Chinese medicine injection approved by the China Food and Drug Administration for use as stroke first aid in ambulances, Xingnaojing Injection (XNJI) has been widely used in cases of both acute ischemic stroke (IS) and intracerebral hemorrhage (ICH). However, there is no robust clinical evidence regarding the efficacy and safety of the early use of XNJI during stroke first aid. The main purpose of this trial is to observe whether XNJI, intravenously administered within 24 h of onset in the prehospital ambulance setting, protects against early neurological deterioration (END) on the third day of onset in patients with acute stroke.Methods: The Trial of a prehospital intervention with traditional Chinese medicine for acute stroke (TRACE) is a Mixed-Methods research (MMR) study that involves a combination of quantitative and qualitative research. The quantitative research part of this project is a prospective, multicenter, observational, clinical registry study, for which we aimed to recruit 1,000 patients with acute stroke (IS and ICH). Based on our observation of whether XNJI was intravenously administered within 24 h of onset in the prehospital ambulance setting, patients with acute stroke will be divided into two groups: the exposure group comprising patients who were intravenously administered XNJI and the nonexposure group comprising patients who were not. The primary outcome is early neurological deterioration (END) on the third day of onset defined as an increase of 2 or more points in the National Institute of Health Stroke Scale score between baseline and day 3. In addition, based on the aforementioned quantitative research, qualitative research will be conducted by interviewing emergency doctors about their knowledge and attitude regarding XNJI used for stroke first aid.Discussion: The results of the TRACE study will provide preliminary evidence for the relationship between XNJI used within 24 h of onset and the presence of END on the third day after stroke onset; it will aid in improving the current knowledge regarding the early use of XNJI for stroke first aid.Clinical Trial Registration:clinicaltrials.gov, identifier NCT04275349